Pathology Assessments of Multiple Organs in Fatal COVID-19 in Intensive Care Unit vs. Non-intensive Care Unit Patients - Zerbib, Yoann; Guilain, Nelly; Eymieux, Sébastien; Uzbekov, Rustem; Castelain, Sandrine; Blanchard, Emmanuelle; François, Catherine; Chatelain, Denis; Brault, Clément; Maizel, Julien; Roingeard, Philippe; Slama, Michel (Frontiers in Medicine, 2022)
Purpose The objective of the present study was to provide a detailed histopathological description of fatal coronavirus disease 2019 (COVID 19), and compare the lesions in Intensive Care Unit (ICU) and non-ICU patients. Methods In this prospective study we included adult patients who died in hospital after presenting with confirmed COVID-19. Multiorgan biopsies were performed. Data generated with light microscopy, transmission electron microscopy (TEM) and RT-PCR assays were reviewed. Results 20 patients were enrolled in the study and the main pulmonary finding was alveolar damage, which was focal in 11 patients and diffuse in 8 patients. Chronic fibrotic and inflammatory lesions were observed in 18 cases, with acute inflammatory lesions in 12 cases. Diffuse lesions, collapsed alveoli and dystrophic pneumocytes were more frequent in the ICU group (62.5%, vs. 25%; 63%, vs. 55%; 87.5%, vs. 54%). Acute lesions (82%, vs. 37.5%; p = 0.07) with neutrophilic alveolitis (63.6% vs. 0%, respectively; p = 0.01) were observed more frequently in the non-ICU group. Viral RNA was detected in 12 lung biopsies (60%) up to 56 days after disease upset. TEM detected viral particles in the lung and kidney biopsy samples up to 27 days after disease upset. Furthermore, abundant networks of double-membrane vesicles (DMVs, a hallmark of viral replication) were observed in proximal tubular epithelial cells. Conclusion Lung injury was different in ICU and non-ICU patients. Extrapulmonary damage consisting in kidney and myocardial injury were more frequent in ICU patients. Our TEM experiments provided the first description of SARS-CoV-2-induced DMVs in kidney biopsy samples—a sign of intense viral replication in this organ.